Acupuncture Improves Endometrial Angiogenesis by Activating PI3K/AKT Pathway in a Rat Model with PCOS. (24th August 2022) - Xing, Liwei; Chen, Yang; He, Zhe; He, Ming; Sun, Yuhuan; Xu, Jinlong; Wang, Jian; Zhuang, Haina; Ren, Zeqin; Chen, Ying; Yang, Jun; Cheng, Shuluo; et al.
Abstract : Background . Acupuncture, a treatment derived from traditional Chinese medicine, can effectively relieve the symptoms and improve pregnancy outcome in patients with polycystic ovary syndrome (PCOS); however, its mechanism remains unclear. This study aimed at investigating whether acupuncture could improve endometrial angiogenesis and thus endometrial receptivity via activating PI3K/AKT pathway in PCOS rats. Methods . We established a rat model with PCOS, which was induced by DHEA. Acupuncture was performed every other day for 15 days, and the PI3K inhibitor (LY294002) was intraperitoneal injected 30 mins before acupuncture treatment. Females rats were mated with male SPF SD rats in a ratio of 2 : 1 after treatment and sacrificed on the 5th day when the vaginal plug was identified. The number of implantation sites was observed, followed by ovarian and endometrial morphology detected with hematoxylin-eosin staining and a scanning electron microscope, estrous cycle detected with vaginal smear analysis, and sex hormones and angiogenesis-related PI3K/AKT gene/protein expression detected with enzyme-linked immunosorbent assay, western blotting, immune histochemistry, and quantitative real-time PCR. Results . Acupuncture notably improved implantation sites' number, endometrial receptivity factors including endometrial morphology, pinopodes, HOX-10, and LIF protein expression, as well as angiogenesis and PI3K/AKT pathway factors such as VEGF, VEGFR2, Ang-1, PI3K, AKT, and P-AKT gene/protein expression and the level of eNOS and NO in the endometrium of rats with PCOS; PCOS-like symptoms were alleviated as well. The efficacy of acupuncture on a rat model with PCOS was counteracted by the combination with the PI3K inhibitor. Conclusion . Acupuncture improves endometrial angiogenesis by activating the PI3K/AKT pathway, thus promoting endometrial receptivity and the number of implantation sites in rats with PCOS.